COMMUTING TO SCHOOL OF 9 YEARS OLD PUPILS IN SLOVENIA - Ivan Čuk; Almir Atiković; Mojca Peček (Sport Scientific And Practical Aspects, 2025)
With our investigation we wanted to find the proportion of pupils who are practicing active commuting to school, and the reasons why some children are not active and how they fell about active commuting. Subject’s sample consisted of 232 pupils of who were attending 3 and 4 class (average age=8.7 years). Pupils had to answer on 46 closed questions, two of them were open. According to the results we can conclude: Slovene children are active commuters to/from school; children who are not active commuters, are driven to/from school because of parents drive them, they live to far and the traffic is to busy; children who are not active commuters would became ones if they would live closer to school, and the traffic would be less busy and if there would be more safe places to cross the road.